PENGEMBANGAN BAHAN AJAR MATERI USAHA DAN ENERGI MODEL PEMBELAJARAN EXPERIENTIAL DENGAN PENDEKATAN KONTEKSTUAL - Fintika Kurnia Sari; Tineke Makahinda; Theresje Mandang (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to develop teaching materials for work and energy in the form of modules using an experiential learning model with a contextual approach in improving the learning processes and outcomes of SMA Negeri 2 Tondano students. This research was conducted at SMA Negeri 2 Tondano. The research method used is the research and development method by following the stages of Borg and Gall. The development steps are as follows: 1) preliminary study, 2) development study, 3) product testing and model validation. Based on the results of device validation from material experts and media experts, learning tools reached 100% and 95.83%, respectively, so that they were included in the very valid criteria. The results of the student response questionnaire on the display aspect with a percentage of 86%, the presentation aspect of the material is 81%, and the benefits aspect is 84%, and the student learning outcomes based on the average comparison of the pretest and posttest scores respectively are 27.79 and 75.92. So that the development of experiential learning model teaching materials with a contextual approach is quite effective in improving student learning processes and outcomes.